2010
DOI: 10.1111/j.1471-4159.2010.06583.x
|View full text |Cite
|
Sign up to set email alerts
|

Bivalent phenethylamines as novel dopamine transporter inhibitors: evidence for multiple substrate‐binding sites in a single transporter

Abstract: J. Neurochem. (2010) 112, 1605–1618. Abstract Bivalent ligands – compounds incorporating two receptor‐interacting moieties linked by a flexible chain – often exhibit profoundly enhanced binding affinity compared with their monovalent components, implying concurrent binding to multiple sites on the target protein. It is generally assumed that neurotransmitter sodium symporter (NSS) proteins, such as the dopamine transporter (DAT), contain a single domain responsible for recognition of substrate molecules. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
49
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 47 publications
11
49
0
Order By: Relevance
“…Releasers are BAT substrates, and the inward transport of a BAT substrate, together with Na ϩ and Cl Ϫ , leads to the countertransport of endogenous neurotransmitter out of the nerve terminal. Resolution of the structure of the bacterial LeuT Aa transporter (Yamashita et al, 2005;Shi et al, 2008) identified two substrate binding sites (S1 and S2), suggesting that the BATs might also possess two substrate binding sites, where the binding of a substrate to S2 triggers the release of substrate bound to S1 and Na ϩ into the intracellular compartment (Nyola et al, 2010;Schmitt et al, 2010). These findings emphasize the importance of conformational changes to transporter function (Ferrer and Javitch, 1998;Reith et al, 2001;Gether et al, 2006) Fig.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Releasers are BAT substrates, and the inward transport of a BAT substrate, together with Na ϩ and Cl Ϫ , leads to the countertransport of endogenous neurotransmitter out of the nerve terminal. Resolution of the structure of the bacterial LeuT Aa transporter (Yamashita et al, 2005;Shi et al, 2008) identified two substrate binding sites (S1 and S2), suggesting that the BATs might also possess two substrate binding sites, where the binding of a substrate to S2 triggers the release of substrate bound to S1 and Na ϩ into the intracellular compartment (Nyola et al, 2010;Schmitt et al, 2010). These findings emphasize the importance of conformational changes to transporter function (Ferrer and Javitch, 1998;Reith et al, 2001;Gether et al, 2006) Fig.…”
Section: Discussionmentioning
confidence: 69%
“…The increased concentration of internal cellular sodium at the transporter also facilitates reverse transport of dopamine (Goodwin et al, 2009;Pifl et al, 2009). Recent data suggest that the model developed on the basis of the LeuT Aa transporter may also apply to the biogenic amine transporters (Schmitt et al, 2010). In addition, other mechanisms, such as receptor phosphorylation and substrate-induced currents, can affect substrate-mediated neurotransmitter efflux (Sitte and Freissmuth, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The low affinity site could be a specific to a transition state, which would also explain the higher turnover rate for GlcUA transport. A two-binding site model with different binding affinities for different substrates is not unprecedented as it has been proposed for the bacterial LeuT transporter (45) and the human dopamine transporter (46). Interestingly, two substrate binding sites have been identified in VGLUT1 through docking studies and molecular dynamic stimulation (14).…”
Section: Glcua and K Imentioning
confidence: 99%
“…S3) (8, 10, 11). Several studies have shown that the equivalent site in monoamine transporters can accommodate inhibitors (17,18,25,26), and mutations of S2 residues in SERT and NET have been found to perturb inhibitor affinity (10,11). To explore whether talopram binds within the S2 site in NET, we introduced 32 single-point mutations into 16 different residues within or in close proximity of the S2 site (Fig.…”
Section: Talopram Is Largely Unaffected By Mutations In the Extracellmentioning
confidence: 99%